Impact of Climate Change on Animal Health and Production - Gebremichael, Bashahun; Kefyalew , Dese; Mulatu , Zerihun; Abdurahaman , Mukerim; Tafese, Wubit (International Journal of Climatic Studies, 2023)
Purpose: To examine the impact of climate change on animal health and production. Methodology: To review an existing literatures concerning impact of climate change on animal health and production. Findings: Climate change is seen as a major threat to the survival of many species of animal, ecosystems and the sustainability of livestock production systems globally. Livestock production and health are considerably vulnerable to the impact of climate change. Since several decades back, climate change has become the major issue affecting global and regional ecosystems and people are working on it. Although yet it is real and is happening with concomitant changes in precipitation, flooding, heavy winds, and the frequency of severe events, increased temperature, and changes in humidity. It is evidenced that it will become worse in the future life. Climate change has direct and indirect impacts on emerging and re-emerging animal diseases and zoonoses since it disrupts natural ecosystems and allows disease-causing pathogens to move into new areas where they may harm wild life, domestic species, and humans. The interaction between animal production and climate change is complex since animal production contributes to climate change. However to the reverse and worse condition, climate change highly affects animal production. Thus, the increased threat of climate change on the animal production and health sectors needs the hands of various stakeholders to work collaboratively.